Pengaruh Model Role Playing Berbantuan Media Augment Reality Assemblr Edu Terhadap Hasil Belajar Kognitif Siswa Mata Pelajaran Pendidikan Pancasila di Kelas III SDN 1 Cigadung (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the effect of the role-playing model assisted by augmented reality media assemblr edu on the cognitive learning outcomes of students in the Pancasila education subject in grade III of SD Negeri 1 Cigadung before and after the implementation of the role-playing model assisted by augmented reality media assemblr edu. This research uses a quantitative method, this type of research is a Quasi-Experiment with a non-equivalent control group design. The sampling technique in this study is purposive random sampling. This research involves 42 students from grade III of SD Negeri 1 Cigadung. The samples studied consist of 42 students from classes III A and III B. Data collection was conducted through pre-tests and post-tests consisting of ten questions, observations, interviews, and documentation. The data analysis technique used is the t-test. The results of the study indicate that the role playing model assisted by the media augmented reality assembler edu can improve students' cognitive learning outcomes. Statistical tests show a two-sided significance level of 0.000, below 0.05. If the two-sided significance value is less than 0.05, then the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This shows that the role-playing model assisted by the augmented reality media assembly edu affects students' cognitive learning outcomes.